Addressing Impact of Counseling Research: A Comparative Study of Counseling and Psychology Journals. (3rd July 2018) - Hunter, Quentin; Balkin, Richard S.; Reiner, Summer M.
ABSTRACT: Counseling researchers, who often work for institutions that place significant value on journal impact factor (JIF), are faced with the choice to publish their manuscripts in professional counseling journals or those of other professions that might have higher JIFs. Publication and journal impact factor data for 6 American Counseling Association journals and 58 American Psychological Association journals were examined. Although both groups compared on issues per year and rejection rates, counseling journals averaged fewer articles per year and lower average impact factor. Implications and recommendations for increasing impact of counseling research publications are discussed.